The neuropeptide NLP-22 regulates a sleep-like state in Caenorhabditis elegans - Nelson, MD (2013)
Neuropeptides play central roles in the regulation of homeostatic behaviors such as sleep and feeding. Caenorhabditis elegans displays sleep-like quiescence of locomotion and feeding during a larval transition stage called lethargus and feeds during active larval and adult stages. Here we show that the neuropeptide NLP-22 is a regulator of Caenorhabditis elegans sleep-like quiescence observed during lethargus. nlp-22 shows cyclical mRNA expression in synchrony with lethargus; it is regulated by LIN-42, an orthologue of the core circadian protein PERIOD; and it is expressed solely in the two RIA interneurons. nlp-22 and the RIA interneurons are required for normal lethargus quiescence, and forced expression of nlp-22 during active stages causes anachronistic locomotion and feeding quiescence. Optogenetic stimulation of RIA interneurons has a movement-promoting effect, demonstrating functional complexity in a single neuron type. Our work defines a quiescence-regulating role for NLP-22 and expands our knowledge of the neural circuitry controlling Caenorhabditis elegans behavioral quiescence.